A method for preparing ultrafine square cobalt oxalate and ultrafine quasi-spherical cobalt powder
By regulating the growth rate of cobalt oxalate grains, ultrafine square cobalt oxalate with small particle size and excellent morphology was prepared, which solved the problem of poor morphology of cobalt powder in the existing technology, and achieved the preparation of high-quality cobalt powder to meet the needs of cemented carbide.
Patent Information
- Application Number
- CN202411629413.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art is difficult to prepare cobalt oxalate with small particle size and excellent morphology, resulting in the morphology of the cobalt powder being dendritic, limiting its application in cemented carbides.
By providing a mixed solution of oxalate and cobalt-containing ions, performing a precipitation reaction and controlling the growth rate of cobalt oxalate grains, ultrafine square cobalt oxalate with small particle size and square particles is prepared as the precursor of high-quality cobalt powder.
The ultrafine square cobalt oxalate with Fischer's particle size is less than 1 μm. As a good precursor for high-purity cobalt powder, it meets the requirements of cemented carbide for cobalt powder, simplifies the process flow and reduces the amount of wastewater.
Smart Images

Figure CN119143595B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nonferrous metal production, and in particular relates to a method for preparing ultrafine square cobalt oxalate and ultrafine quasi-spherical cobalt powder. Background Art
[0002] Cobalt powder has excellent properties such as high chemical activity, good electrical conductivity, magnetism and high temperature resistance, and has extremely important applications in the field of cemented carbide. Studies have shown that the morphology and particle size of cobalt powder have an important influence on the mechanical properties of cemented carbide. Among them, spherical cobalt powder particles have the lowest porosity and ductility, and can show good miscibility when mixed with other raw materials of cemented carbide; and fine-grained cobalt powder can significantly improve the bonding, strength and toughness of cemented carbide. Therefore, cobalt powder with spherical or quasi-spherical morphology and fine particles (Fisher particle size less than 1.0 micron) can better meet the requirements of cemented carbide.
[0003] At present, the cobalt powder is usually prepared by pyrolysis using cobalt carbonate precipitate or cobalt oxalate precipitate as the cobalt precursor. Since the particle size and morphology of cobalt powder are relatively highly dependent on the cobalt precursor, the preparation of a cobalt precursor with small particle size and good morphology is the key to preparing high-quality cobalt powder and high-quality cemented carbide.
[0004] Compared with cobalt carbonate precipitates, which are prone to carry impurity ions during the precipitation process and have poor crystallinity, cobalt oxalate precipitates have better crystallinity and uniformity, are easier to wash and separate solids and liquids, and are easy to obtain products of higher purity. They are the preferred cobalt precursor for preparing high-purity ultrafine cobalt powder. However, the growth direction of the crystal face of cobalt oxalate crystals is single, and the morphology of cobalt oxalate prepared by precipitation is often mainly long rods or fibers, and the particles are coarse, resulting in the cobalt powder generated by pyrolysis often being dendritic, which limits its application in cemented carbide. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing ultrafine square cobalt oxalate and ultrafine quasi-spherical cobalt powder. The present invention suppresses the unidirectional growth of cobalt oxalate crystals and regulates the growth rate of cobalt oxalate grains to prepare cobalt oxalate powder with small particle size and square particles, which provides a good precursor for preparing ultrafine quasi-spherical cobalt powder and is conducive to meeting the requirements of cemented carbide for cobalt powder.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing ultrafine square cobalt oxalate, comprising the following steps:
[0008] Providing an oxalate-containing mixed solution, wherein the oxalate-containing mixed solution comprises oxalic acid and soluble oxalate;
[0009] Providing a mixed solution containing cobalt ions, wherein the mixed solution containing cobalt ions comprises a soluble cobalt salt and a nonionic surfactant having an oxygen-containing group, to obtain a mixed solution containing cobalt ions;
[0010] The cobalt ion-containing mixed solution and the oxalate-containing mixed solution are mixed to generate a precipitation reaction, the obtained reaction liquid is subjected to solid-liquid separation, and a solid material is collected;
[0011] The solid material is dried to obtain the ultrafine square cobalt oxalate; the ultrafine square cobalt oxalate has a Fisher particle size of less than 0.8 μm.
[0012] Preferably, the soluble oxalate comprises at least one of sodium oxalate, potassium oxalate and ammonium oxalate.
[0013] Preferably, the mass ratio of oxalic acid to soluble oxalate is 2.0-20.0:1.
[0014] Preferably, the soluble cobalt salt includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate.
[0015] Preferably, the nonionic surfactant having oxygen-containing groups includes at least one of Triton X-100, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, crown ether, polyoxyethylene alkylamine and polysorbate 80.
[0016] Preferably, the mass ratio of the nonionic surfactant having oxygen-containing groups to the soluble cobalt salt is 0.001-0.2:1.
[0017] Preferably, the precipitation reaction is carried out under conditions of ultrasound and / or mechanical stirring; the frequency of the ultrasound is 4 to 40 kHz.
[0018] Preferably, the precipitation rate of the precipitation reaction is 10-100%.
[0019] Preferably, the precipitation reaction temperature is 10-35°C, and the time is 20-90 min; the drying temperature is 25-105°C, and the time is 2-24 h.
[0020] The present invention provides a method for preparing ultrafine spherical cobalt powder, comprising the following steps:
[0021] Under a hydrogen atmosphere, ultrafine square cobalt oxalate is subjected to a reduction reaction to obtain the ultrafine quasi-spherical cobalt powder; the ultrafine square cobalt oxalate is the ultrafine square cobalt oxalate obtained by the preparation method described in the above technical solution; the ultrafine quasi-spherical cobalt powder has a Fisher particle size of less than 0.8 μm.
[0022] The invention provides a method for preparing ultrafine square cobalt oxalate, comprising the following steps: providing an oxalate-containing mixed solution, wherein the oxalate-containing mixed solution comprises oxalic acid and soluble oxalate; providing a cobalt ion-containing mixed solution, wherein the cobalt ion-containing mixed solution comprises a soluble cobalt salt and a non-ionic surfactant having an oxygen-containing group; mixing the cobalt ion-containing mixed solution with an oxalate-containing mixed solution to generate a precipitation reaction, performing solid-liquid separation on the obtained reaction liquid, and collecting solid materials; drying the solid materials to obtain the ultrafine square cobalt oxalate; and the ultrafine square cobalt oxalate has a Fisher particle size of less than 1 μm. In the present invention, the molecular structure of the nonionic surfactant has an oxygen-containing group. After the nonionic surfactant is mixed with a saturated cobalt salt solution, the oxygen lone pair electrons on the oxygen-containing group can form a coordination structure with the cobalt ions containing empty orbitals. This coordination structure increases the desolvation energy of the cobalt ions, prevents the high aggregation of the cobalt ions, and can refine the formed cobalt oxalate grains, controlling their Fisher particle size below 1 μm. At the same time, the nonionic surfactant molecules with oxygen-containing groups have a steric hindrance effect on the diffusion of cobalt ions, and the growth process of a single crystal face is significantly inhibited, thereby regulating the morphology of the cobalt oxalate to a square shape.
[0023] Moreover, the present invention creatively adopts a saturated cobalt salt solution and a saturated oxalic acid-oxalate mixed solution as raw materials, which can maximize the concentration of reactive ions, increase the number of crystal nuclei, inhibit the growth rate of cobalt oxalate crystals in a single direction, and is conducive to the generation of ultrafine cobalt oxalate crystals; and greatly reduce the amount of wastewater in the preparation process.
[0024] Furthermore, the nonionic surfactant with oxygen-containing groups described in the present invention includes at least one of Triton X-100, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, crown ether, polyoxyethylene alkylamine and polysorbate-80. The element types of these nonionic surfactants mainly include C, O, and H. Impurity ions will not be introduced during the precipitation process, the purity of cobalt oxalate will not be affected, and the production process is simple and efficient.
[0025] Furthermore, in the present invention, the cobalt oxalate precipitation process has strong applicability, a simple and efficient process, and can be directly applied in industry without changing the equipment and raw materials used in the process.
[0026] Furthermore, the present invention selectively removes other metal impurity ions (such as nickel, iron, copper, zinc, calcium, magnesium, manganese, etc.) in the system by controlling the precipitation rate to achieve the effect of separation and purification, and the impurity amount of the obtained ultrafine square cobalt oxalate is less than 10ppm, which is conducive to the preparation of high-purity cobalt powder. In a hydrogen atmosphere, the cobalt oxalate prepared by the present invention is used as a precursor for reduction reaction, and the obtained cobalt powder is spherical. Compared with the fibrous cobalt oxalate prepared by the existing process, the square cobalt oxalate prepared by the present invention is more conducive to the production of cobalt powder required for cemented carbide. Therefore, the method provided by the present invention can not only maintain a good purity of cobalt oxalate, but also provide a good precursor for the preparation of ultrafine spherical cobalt powder, which is conducive to the simple, efficient and low-cost preparation of high-quality cobalt powder with better fluidity and capable of promoting dense pressing, which is conducive to meeting the demand for high-quality cobalt powder in high-end manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 This is a SEM image of the cobalt oxalate obtained in Example 1;
[0029] Figure 2 This is the XRD pattern of cobalt oxalate obtained in Example 1;
[0030] Figure 3 This is the SEM image of the cobalt powder obtained in Example 2;
[0031] Figure 4 This is a SEM image of the cobalt oxalate obtained in Example 3;
[0032] Figure 5 This is a SEM image of cobalt oxalate obtained in Example 4;
[0033] Figure 6 This is a SEM image of the cobalt oxalate obtained in Example 5;
[0034] Figure 7 This is a SEM image of cobalt oxalate obtained in Comparative Example 1;
[0035] Figure 8 This is the SEM image of the cobalt oxalate obtained in Comparative Example 2. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing ultrafine square cobalt oxalate, comprising the following steps:
[0037] Providing an oxalate-containing mixed solution, wherein the oxalate-containing mixed solution comprises oxalic acid and soluble oxalate;
[0038] Providing a mixed solution containing cobalt ions, wherein the mixed solution containing cobalt ions comprises a soluble cobalt salt and a nonionic surfactant having an oxygen-containing group, to obtain a mixed solution containing cobalt ions;
[0039] The cobalt ion-containing mixed solution and the oxalate-containing mixed solution are mixed to generate a precipitation reaction, the obtained reaction liquid is subjected to solid-liquid separation, and a solid material is collected;
[0040] The solid material is dried to obtain the ultrafine square cobalt oxalate; the ultrafine square cobalt oxalate has a Fisher particle size of less than 1 μm.
[0041] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0042] In the present invention, the oxalate-containing mixed solution contains oxalic acid and soluble oxalate. In the present invention, the soluble oxalate may include at least one of sodium oxalate, potassium oxalate and ammonium oxalate; the sodium oxalate may be sodium oxalate hydrate, the potassium oxalate may be potassium oxalate hydrate, and the ammonium oxalate may be ammonium oxalate hydrate. In a specific embodiment of the present invention, the soluble oxalate may be ammonium oxalate, potassium oxalate or ammonium oxalate. In the present invention, the mass ratio of oxalic acid to soluble oxalate may be 2.0~20.0:1; in a specific embodiment of the present invention, the oxalic acid is dihydrated oxalic acid; the material-liquid ratio of the soluble oxalate, dihydrated oxalic acid and water is 2.7g:12.8~12.9g:81mL. In a specific embodiment of the present invention, oxalic acid, soluble oxalate and water may be mixed under ultrasonic conditions to obtain an oxalate-containing mixed solution. In a specific embodiment of the present invention, the frequency of the ultrasound may be 40kHz. In an embodiment of the present invention, at 25°C, the concentration of oxalate in the oxalate-containing mixed solution is 103 g / L, which is saturated. In the present invention, oxalic acid and oxalate in the oxalate-containing mixed solution are saturated, which can increase the number of crystal nuclei; wherein oxalic acid can provide a large amount of oxalate as a precipitant, and oxalate can enhance the solution ion strength while providing the oxalate precipitant; in the subsequent precipitation reaction, oxalate reacts with cobalt salt to generate cobalt oxalate.
[0043] In the present invention, the cobalt ion-containing mixed solution contains a soluble cobalt salt and a nonionic surfactant having an oxygen-containing group. In the present invention, the soluble cobalt salt may include at least one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate; the cobalt sulfate may be a cobalt sulfate hydrate, the cobalt nitrate may be a cobalt nitrate hydrate, the cobalt chloride may be a cobalt chloride hydrate, and the cobalt acetate may be a cobalt acetate hydrate. In a specific embodiment of the present invention, the soluble cobalt salt may be cobalt sulfate, cobalt nitrate, cobalt chloride or cobalt acetate. In an embodiment of the present invention, under the condition of 25°C, the concentration of cobalt ions in the cobalt ion-containing mixed solution is 250g / L, which is in a saturated state. In the present invention, a soluble cobalt salt, water and a nonionic surfactant having an oxygen-containing group may be mixed under ultrasonic and / or mechanical stirring conditions to obtain a cobalt ion-containing mixed solution. In a specific embodiment of the present invention, a soluble cobalt salt and water may be mixed under ultrasonic conditions to obtain a saturated cobalt salt solution; the saturated cobalt salt solution is mixed with a nonionic surfactant having an oxygen-containing group under mechanical stirring conditions to obtain a cobalt ion-containing mixed solution. In a specific embodiment of the present invention, the frequency of the ultrasound can be 40kHz; the rate of the mechanical stirring can be 300rpm. The pH value of the saturated cobalt salt solution of the present invention can be 1.0~7.0; in a specific embodiment, the pH value of the saturated cobalt salt solution can be 1.0, 2.0, 3.0, 4.0, 5.0, 6.0 or 7.0. The purity of the cobalt salt of the present invention can be 99.99%. In the present invention, with a cobalt salt of 99.99% purity as a reactant, the purity of cobalt oxalate after precipitation can reach 99.999%. In the present invention, the non-ionic surfactant having an oxygen-containing group can include at least one of Triton X-100, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, crown ether, polyoxyethylene alkylamine and polysorbate-80 (tween-80); in a specific embodiment, the non-ionic surfactant having an oxygen-containing group can be Triton X-100 or polysorbate-80. In the present invention, the molecular formula of Triton X-100 is: C8H 17C6H4(OCH2CH2)nOH(n≈10), molecular weight is about 647; polysorbate-80 has a molecular weight of about 1309.66. The mass ratio of the nonionic surfactant having oxygen-containing groups to the soluble cobalt salt of the present invention can be 0.01~0.2:1; in a specific embodiment, the mass ratio of the nonionic surfactant having oxygen-containing groups to the saturated cobalt salt solution is 0.02:1. In the present invention, the molecular structure of the nonionic surfactant has oxygen-containing groups. After the nonionic surfactant is mixed with the saturated cobalt salt solution, the oxygen lone pair electrons on the oxygen-containing groups can form a coordination structure with the cobalt ions containing empty orbitals. This coordination structure increases the desolvation energy of the cobalt ions, prevents the high aggregation of the cobalt ions, and can refine the obtained cobalt oxalate grains, and control its Fisher particle size below 1μm; at the same time, the nonionic surfactant molecules having oxygen-containing groups have a steric hindrance effect on the diffusion of cobalt ions, and the growth process of a single crystal face is significantly inhibited, thereby regulating the morphology of cobalt oxalate to a square.
[0044] The present invention mixes the cobalt ion mixed solution with the oxalate mixed solution to cause a precipitation reaction, separates the obtained reaction liquid into solid and liquid, and collects solid materials. The present invention does not specifically limit the mixing order of the cobalt ion mixed solution and the oxalate mixed solution. The cobalt ion mixed solution can be added to the oxalate mixed solution, or the oxalate mixed solution can be added to the cobalt ion mixed solution, or the cobalt ion mixed solution and the oxalate mixed solution can be added simultaneously and mixed. In a specific embodiment of the present invention, the oxalate mixed solution is added to the cobalt ion mixed solution; the addition rate of the oxalate mixed solution can be 10~200mL / s, specifically 10mL / s, 50mL / s, 100mL / s, 150mL / s or 200mL / s. In the present invention, the precipitation reaction can be carried out under the conditions of ultrasound and / or mechanical stirring; in a specific embodiment, the precipitation reaction is carried out under the conditions of ultrasound and mechanical stirring. In the present invention, the frequency of the ultrasound can be 4-40kHz, and the rate of the mechanical stirring can be 200-400rpm; in a specific embodiment, the frequency of the ultrasound can be 4kHz, 10kHz, 20kHz, 30kHz or 40kHz, and the rate of the mechanical stirring can be 200rpm, 250rpm, 300rpm, 350rpm or 400rpm. In the present invention, the temperature of the precipitation reaction can be 10-35°C, and the time can be 20-90min; in a specific embodiment of the present invention, the temperature of the precipitation reaction can be 10°C, 25°C or 35°C, and the time can be 20min, 40min, 50min, 70min or 90min. In the present invention, the precipitation rate of the precipitation reaction can be 10-100%; in a specific embodiment, the precipitation rate of the precipitation reaction can be 10%, 50%, 80% or 100%. In the present invention, the precipitation rate is the molar ratio of oxalate ions to cobalt ions; controlling the precipitation rate within the range of 10-100% can improve the purity of cobalt oxalate.
[0045] In the present invention, the solid-liquid separation method can be centrifugation, filtration or suction filtration. After obtaining the solid material, the present invention can wash the solid material with water, and then dry the washed solid material to obtain the ultrafine square cobalt oxalate. In the present invention, the drying temperature can be 25~105℃, and the time can be 2~24h; in a specific embodiment, the drying temperature can be 25℃, 40℃, 60℃, 80℃ or 105℃, and the time can be 2h, 12h or 24h.
[0046] The ultrafine square cobalt oxalate of the present invention has a Fischer-Tropsch particle size of less than 1 μm. In a specific embodiment, the ultrafine square cobalt oxalate has a Fischer-Tropsch particle size of 0.66 μm, 0.79 μm, 0.81 μm or 0.95 μm.
[0047] The present invention also provides a method for preparing ultrafine quasi-spherical cobalt powder, comprising the following steps: subjecting ultrafine square cobalt oxalate to a reduction reaction in a hydrogen atmosphere to obtain the ultrafine quasi-spherical cobalt powder; the ultrafine square cobalt oxalate is the ultrafine square cobalt oxalate obtained by the preparation method described in the above technical solution; the ultrafine quasi-spherical cobalt powder has a Fisher particle size of less than 0.8 μm.
[0048] In the present invention, the flow rate of the hydrogen can be 0.1~1.0L / min; in a specific embodiment, the flow rate of the hydrogen can be 0.2L / min, 0.4L / min, 0.6L / min, 0.8L / min or 1.0L / min. In the present invention, the temperature of the reduction reaction can be 380~500℃, and the insulation time can be 1~3h; the rate of heating to the temperature of the reduction reaction can be 4~6℃ / min; in a specific embodiment, the temperature of the reduction reaction can be 400℃, 450℃ or 470℃, the insulation time can be 1h, 2h or 3h, and the rate of heating to the temperature of the reduction reaction can be 4℃ / min, 5℃ / min or 6℃ / min. In an embodiment of the present invention, after the reduction reaction is completed, the temperature is reduced to room temperature to obtain the ultrafine spherical cobalt powder.
[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] The molecular formula of Triton X-100 used in the embodiment is: C8H 17 C6H4(OCH2CH2)nOH(n≈10), molecular weight is about 647; molecular weight of polysorbate-80 is about 1309.66.
[0051] Example 1
[0052] (1) At 25°C, 27 g of ammonium oxalate and 128.8 g of oxalic acid dihydrate (super pure) were mixed with 810 mL of deionized water and dissolved by ultrasonication to prepare a saturated oxalic acid-ammonium oxalate solution (hereinafter referred to as solution A). The concentration of oxalate in solution A was 103 g / L (saturated).
[0053] (2) At 25°C, 334 mL of deionized water and 448 g of cobalt nitrate hexahydrate (purity: 99.990%) were mixed and dissolved by ultrasonication to obtain a saturated cobalt nitrate solution (hereinafter referred to as solution B). Triton X-100 was then added to the solution B (the mass of Triton X-100 accounted for 2% of the mass of solution B), and the Triton X-100 was fully dissolved by stirring to obtain a saturated cobalt salt-nonionic surfactant solution (hereinafter referred to as solution C), wherein the concentration of cobalt ions in solution C was 250 g / L (saturated state).
[0054] (3) Adding the solution A to the solution C at a rate of 150 mL / s under the conditions of an ice bath (temperature of 10° C.), mechanical stirring (rate of 300 rpm) and ultrasound (frequency of 40 kHz), after the solution A is added to the solution C, a pink solid begins to form in the system; starting from the time when the solution A is added, the precipitation reaction is continued for 30 minutes under the above conditions of ice bath, mechanical stirring and ultrasound. After the reaction is completed, the precipitate is collected from the obtained reaction solution by suction filtration, and the precipitate is washed with ultrapure water. The washed precipitate is then dried at 80° C. to obtain cobalt oxalate (precipitation rate is 80%).
[0055] The SEM image of cobalt oxalate obtained in Example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the cobalt oxalate obtained in Example 1 has a uniform square particle shape, a Fisher particle size D50 of 0.79 μm, and a purity of 99.9991%.
[0056] The X-ray diffraction spectrum (XRD) of cobalt oxalate obtained in Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the cobalt oxalate obtained in the example contains two crystal waters, and the crystal form is mainly β-type.
[0057] Example 2
[0058] The cobalt oxalate obtained in Example 1 was placed in a rotary atmosphere tubular furnace, hydrogen was introduced therein (flow rate was 0.4 L / min), the temperature was uniformly increased to 450°C at a rate of 5°C / min, and the temperature was kept at 450°C for 2 h to achieve the reduction reaction of cobalt oxalate. After the reduction reaction was completed, the temperature was cooled to room temperature to obtain cobalt powder.
[0059] The SEM image of the cobalt powder obtained in Example 2 is as follows Figure 3 As shown by Figure 3 It can be seen that the cobalt powder obtained in Example 2 has a spherical morphology and a Fisher particle size of 0.65 μm.
[0060] Example 3
[0061] (1) At 25°C, 2.7 g of ammonium oxalate and 12.9 g of oxalic acid dihydrate (super pure) were mixed with 81 mL of deionized water and dissolved by ultrasonication to prepare a saturated oxalic acid-ammonium oxalate solution (hereinafter referred to as solution A). The concentration of oxalate in solution A was 103 g / L (saturated).
[0062] (2) At 25°C, 33.4 mL of deionized water and 44.8 g of cobalt nitrate hexahydrate (purity: 99.990%) were mixed and dissolved by ultrasonication to obtain a saturated cobalt nitrate solution (hereinafter referred to as solution B). Triton X-100 was then added to the solution B (the mass of Triton X-100 accounted for 2% of the mass of solution B), and the Triton X-100 was fully dissolved by stirring to obtain a saturated cobalt salt-nonionic surfactant solution (hereinafter referred to as solution C), wherein the concentration of cobalt ions in solution C was 250 g / L (saturated state).
[0063] (3) Adding the solution A to the solution C at a rate of 150 mL / s under the conditions of an ice bath (temperature of 10° C.), mechanical stirring and ultrasound (ultrasonic frequency of 40 kHz), after the solution A is added to the solution C, a pink solid begins to form in the system; starting from the time when the solution A is added, the precipitation reaction is continued for 30 minutes under the above conditions of ice bath, mechanical stirring and ultrasound. After the reaction is completed, the precipitate is collected from the obtained reaction solution by suction filtration, and the precipitate is washed with ultrapure water. The washed precipitate is then dried at 80° C. to obtain cobalt oxalate.
[0064] The SEM image of cobalt oxalate obtained in Example 3 is as follows Figure 4 As shown by Figure 4 It can be seen that the cobalt oxalate obtained in Example 3 has a uniform square particle shape and a Fisher particle size of 0.81 μm.
[0065] Example 4
[0066] Cobalt oxalate was prepared according to the operating conditions of Example 3, except that the ultrasonic frequency of step (3) was adjusted to 10 kHz. The remaining conditions were the same as those of Example 3.
[0067] The SEM image of cobalt oxalate obtained in Example 4 is as follows Figure 5 As shown by Figure 5 It can be seen that the cobalt oxalate obtained in Example 4 has a uniform square particle shape and a Fisher particle size of 0.66 μm.
[0068] Example 5
[0069] Cobalt oxalate was prepared according to the operating conditions of Example 3, except that the type of non-ionic surfactant was changed from Triton X-100 to polysorbate 80 (tween-80), and the other conditions were the same as those of Example 3.
[0070] The SEM image of cobalt oxalate obtained in Example 5 is as follows Figure 6 As shown by Figure 6 It can be seen that the cobalt oxalate obtained in Example 5 has a uniform square particle shape and a Fisher particle size of 0.95 μm.
[0071] Comparative Example 1
[0072] (1) At 25°C, 2.7 g of ammonium oxalate and 12.9 g of oxalic acid dihydrate (superior purity) were mixed with 81 mL of deionized water and dissolved by ultrasonication to prepare a saturated oxalic acid-ammonium oxalate solution (hereinafter referred to as solution A). The concentration of oxalate in solution A was 103 g / L (saturated state);
[0073] (2) At 25°C, 33.4 mL of deionized water and 44.8 g of cobalt nitrate hexahydrate (purity: 99.990%) were mixed and dissolved by ultrasonication to obtain a saturated cobalt nitrate solution (hereinafter referred to as solution B). The concentration of cobalt ions in solution B was 250 g / L (saturated state);
[0074] (3) Adding the solution A to the solution B at a rate of 150 mL / s under the conditions of an ice bath (temperature of 10° C.), mechanical stirring and ultrasound (ultrasonic frequency of 40 kHz), after the solution A is added to the solution B, a pink solid begins to form in the system; starting from the time when the solution A is added, the precipitation reaction is continued for 30 minutes under the above conditions of ice bath, mechanical stirring and ultrasound. After the reaction is completed, the precipitate is collected from the obtained reaction solution by suction filtration, and the precipitate is washed with ultrapure water. The washed precipitate is then dried at 80° C. to obtain cobalt oxalate.
[0075] The SEM image of cobalt oxalate obtained in Comparative Example 1 is as follows Figure 7 As shown by Figure 7 It can be seen that without adding the non-ionic surfactant having oxygen-containing groups, the cobalt oxalate obtained in Comparative Example 1 has a traditional rod-like morphology, and the morphology is uneven, and the Fisher particle size is relatively large (about 2.5 μm).
[0076] Comparative Example 2
[0077] Cobalt oxalate was prepared according to the operating conditions of Example 3, except that solution A was replaced by an unsaturated oxalic acid-ammonium oxalate solution, specifically composed of 2.7 g ammonium oxalate + 12.9 g oxalic acid dihydrate (superior purity) + 810 ml deionized water; solution B was replaced by an unsaturated cobalt nitrate solution, specifically composed of 33.4 ml deionized water + 448 g cobalt nitrate hexahydrate, and the other conditions were the same as in Example 3.
[0078] The precipitation rate of cobalt oxalate prepared in Comparative Example 2 is 80%, and the SEM image is as follows: Figure 8 As shown by Figure 8 It can be seen that when the concentrations of the oxalic acid solution and the cobalt nitrate solution are non-saturated, the obtained cobalt oxalate is in the traditional long rod shape, and the Fisher particle size is about 8 μm.
[0079] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing ultrafine square cobalt oxalate, characterized in that: The following steps are involved: Providing an oxalate-containing mixed solution, wherein the oxalate-containing mixed solution comprises oxalic acid and soluble oxalate, and mixing a saturated oxalic acid solution with the soluble oxalate to obtain a first mixed solution; A cobalt ion-containing mixed solution is provided, wherein the cobalt ion-containing mixed solution comprises a soluble cobalt salt and a nonionic surfactant having an oxygen-containing group; the nonionic surfactant having an oxygen-containing group comprises at least one of Triton X-100, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, polyoxyethylene alkylamine and polysorbate 80; the mass ratio of the nonionic surfactant having an oxygen-containing group to the soluble cobalt salt is 0.01-0.2:1; and the soluble cobalt salt is a saturated cobalt salt solution; The cobalt ion-containing mixed solution and the oxalate-containing mixed solution are mixed to generate a precipitation reaction, the obtained reaction liquid is subjected to solid-liquid separation, and a solid material is collected; The solid material is dried to obtain the ultrafine square cobalt oxalate; the ultrafine square cobalt oxalate has a Fisher particle size of less than 1 μm.
2. The preparation method according to claim 1, characterized in that: The soluble oxalate includes at least one of sodium oxalate, potassium oxalate and ammonium oxalate.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the oxalic acid to the soluble oxalate is 2.0-20.0:
1.
4. The preparation method according to claim 1, characterized in that: The soluble cobalt salt includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate.
5. The preparation method according to claim 1, characterized in that: The precipitation reaction is carried out under the conditions of ultrasound and / or mechanical stirring; the frequency of the ultrasound is 4-40 kHz.
6. The preparation method according to claim 1, characterized in that: The precipitation rate of the precipitation reaction is 10-100%.
7. The preparation method according to claim 1 or 6, characterized in that: The precipitation reaction temperature is 10-35°C and the time is 20-90min; The drying temperature is 25-105° C. and the drying time is 2-24 hours.
8. A method for preparing ultrafine spherical cobalt powder, characterized in that: The following steps are involved: Under a hydrogen atmosphere, ultrafine square cobalt oxalate is subjected to a reduction reaction to obtain the ultrafine quasi-spherical cobalt powder; the ultrafine square cobalt oxalate is the ultrafine square cobalt oxalate obtained by the preparation method according to any one of claims 1 to 7; the ultrafine quasi-spherical cobalt powder has a Fisher particle size of less than 0.8 μm.
Citation Information
Patent Citations
Method for preparing cobalt powder from cobalt oxalate
CN114433861A